Lectotypifications and new synonyms in Indian Syzygium (Myrtaceae) - Singh, Rajeev Kumar; Arigela, Ravi Kiran (Phytotaxa, 2020)
Three Linnaean names Eugenia jambos, Myrtus caryophyllata and M. zeylanica require second-step lectotypification and are designated here. Fifteen lectotypes and one neotype are also designated for sixteen names of thirteen recognized species of Indian Syzygium. The recently described species Syzygium bournei, S. dhaneshianum and S. lakshmananii are treated here as a new synonym of S. caryophyllatum, S. gardneri and S. montanum respectively.